Oxamflatin Significantly Improves Nuclear Reprogramming, Blastocyst Quality, and In Vitro Development of Bovine SCNT Embryos - Su, Jianmin; Wang, Yongsheng; Li, Yanyan; Li, Ruizhe; Li, Qian; Wu, Yongyan; Quan, Fusheng; Liu, Jun; Guo, Zekun; Zhang, Yong (PLOS ONE, 2011)
Aberrant epigenetic nuclear reprogramming results in low somatic cloning efficiency. Altering epigenetic status by applying histone deacetylase inhibitors (HDACi) enhances developmental potential of somatic cell nuclear transfer (SCNT) embryos. The present study was carried out to examine the effects of Oxamflatin, a novel HDACi, on the nuclear reprogramming and development of bovine SCNT embryos in vitro. We found that Oxamflatin modified the acetylation status on H3K9 and H3K18, increased total and inner cell mass (ICM) cell numbers and the ratio of ICM∶trophectoderm (TE) cells, reduced the rate of apoptosis in SCNT blastocysts, and significantly enhanced the development of bovine SCNT embryos in vitro. Furthermore, Oxamflatin treatment suppressed expression of the pro-apoptotic gene Bax and stimulated expression of the anti-apoptotic gene Bcl-XL and the pluripotency-related genes OCT4 and SOX2 in SCNT blastocysts. Additionally, the treatment also reduced the DNA methylation level of satellite I in SCNT blastocysts. In conclusion, Oxamflatin modifies epigenetic status and gene expression, increases blastocyst quality, and subsequently enhances the nuclear reprogramming and developmental potential of SCNT embryos.